Modeling Inventory Systems Using The User Experience Design Model Method - Nur Fitrianti Fahrudin; Agung Deni Wahyudi (Journal of Data Science and Information Systems, 2023)
Information systems are the process of collecting and processing transaction data and communicating data into information for decision-making. User Experience Design (UXD) is the process of developing a product to increase user satisfaction with a product by increasing usability, accessibility, and satisfaction provided in the interaction with a product or application. The main factor in the success of application developers depends on the user experience that users feel, therefore it is very important to make this a priority in developing designs. This method is able to make your design look neat, simple, intuitive, flexible, and attractive as well as provide a different experience to users of your product or service and make you look unique in front of other competitors. Modeling the inventory system uses a user centered design model with five stages, namely empethized, define problem statements, indentation, and prototype. The results of this study are in accordance with the needs of users in creating a web-based inventory information system that can overcome the problems faced by the school. The results of testing the inventory application using the blackbox testing model which has a value of 100% in accordance with testing the functionality of the system, and the test results using web quality 4.0 obtained a total score of 91.53%. Based on this, the Web Quality 4.0 test results have very good criteria.